William Waller Hening, 1 The Statutes at Large; Being a Collection of All the Laws of Virginia 441 (1808) - (:unkn) unknown (General Publisher, 1657)
Prohibited the giving or selling piece, powder, or shot to “any Indian,” subject to imprisonment and seizure of property.
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES